PENGGUNAAN PEER TEACHING METHOD DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA SISWA KELAS V SDN TUBOKARTO - Rusimah Rusimah; Hesti Sadtyadi; Urip Widodo (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The important components of the learning process at school include the methods, strategies and learning approaches used by teachers. However, in reality there are several problems to achieve the expected goals.  The problems that arise at SDN Tubokarto are that students feel bored and unfocused during teaching and learning activities, in addition, the learning process in the classroom is only dominant on the teacher. The research was conducted in grade V at SDN 1 Tubokarto and grade V at SDN 3 Tubokarto by examining the peer teaching method which aims to provide changes to teaching and learning activities. With this method, it is also expected to be able to improve student learning outcomes and provide many opportunities for students to participate in teaching and learning activities in the classroom, especially in science subjects. The method used is that this research uses experimental research by applying True experimental design. This research applies the post-test only control design type. The results obtained in this test are the error rate of 0.002, which means that the significance value is less than 0.05, so H0 is rejected and Ha is accepted. Which means that learning with the peer teaching method is effectively used in improving learning outcomes in science subjects